PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF DALAM PENDIDIKAN SAINS: ANALISIS BIBLIOMETRIK ALAT DIGITAL (2000-2024) - Mulyono Mulyono; Slamet Sty; Chumdari Chumdari (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
This study aims to analyze the development and trends of global research in the development of interactive learning media for the period 2000-2024. Methods This study uses Bibliometric analysis conducted on 461 articles from the Scopus database using VOSviewer software for visualization and analysis of bibliometric patterns. The results show a significant evolution from the dominance of Computers and Education journals towards the diversification of publication outlets, with Indonesia leading the productivity (105 documents) followed by the United States (95 documents) and China (55 documents). Collaboration analysis reveals the dominant role of Indonesian institutions with the State University of Jakarta (13 publications) as the most productive institution. Keyword mapping identifies areas that are still underexplored in the development of interactive learning media, despite the rapid development of technologies such as virtual reality and artificial intelligence. Despite the shift in digital learning innovation centers from the West to the East, there is still a significant gap in the integration of emergent technology into effective interactive learning media, opening up great opportunities for future research in developing comprehensive digital learning frameworks.